Mangrove forests have various benefits both economically and ecological The excessive uses of mangrove for only fulfilling human needs without replanting will endanger the ecosystem. Deforestation of mangrove forests into aquaculture ponds relates to many factors, both internal and extemal aspects of the aqua culturists. Survey research method was conducted at Jayamukti Village. The research shows that majority of the respondents completed primary education. Even though the level education of a - Tati Hartati; Siti Amanah; Moch Prihatna Sobari (Buletin Ekonomi Perikanan, 2005)
Mangrove forests have various benefits both economically and ecological The excessive uses of mangrove for only fulfilling human needs without replanting will endanger the ecosystem. Deforestation of mangrove forests into aquaculture ponds relates to many factors, both internal and extemal aspects of the aqua culturists. Survey research method was conducted at Jayamukti Village. The research shows that majority of the respondents completed primary education. Even though the level education of aqua culturists is low, the knowledge about the benefits of mangrove is already known, specifically about conservation and fish nursery. From statistical analysis, it can be analyzed that knowledge about the benefits of mangroves positively correlates to respondents' formal education and their experiences about mangrove. Mangroves conservation has a positive correlation with experience about mangroves and local group membership. In addition, response about mangrove rehabilitation rela:as with local aqua culturists membership, formal education and the experiences about mangrove. In order to achieve better aqua culturists behavior in managing mangrove, formal education system. group knowledge in mangrove conservation activity should be improved well.